Synonymous codon usage pattern in model legume Medicago truncatula - Hui SONG; Jing LIU; Tao CHEN; Zhi-biao NAN (Journal of Integrative Agriculture, 2018)
Synonymous codon usage pattern presumably reflects gene expression optimization as a result of molecular evolution. Though much attention has been paid to various model organisms ranging from prokaryotes to eukaryotes, codon usage has yet been extensively investigated for model legume Medicago truncatula. In present study, 39 531 available coding sequences (CDSs) from M. truncatula were examined for codon usage bias (CUB). Based on analyses including neutrality plots, effective number of codons plots, and correlations between optimal codons frequency and codon adaptation index, we conclude that natural selection is a major driving force in M. truncatula CUB. We have identified 30 optimal codons encoding 18 amino acids based on relative synonymous codon usage. These optimal codons characteristically end with A or T, except for AGG and TTG encoding arginine and leucine respectively. Optimal codon usage is positively correlated with the GC content at three nucleotide positions of codons and the GC content of CDSs. The abundance of expressed sequence tag is a proxy for gene expression intensity in the legume, but has no relatedness with either CDS length or GC content. Collectively, we unravel the synonymous codon usage pattern in M. truncatula, which may serve as the valuable information on genetic engineering of the model legume and forage crop.